Given f(x) = 3(x − 4)2

𝑓
(
𝑥
)

=

3
(
𝑥



4
)
2
what is f(3)?

Show your work below

(1 point)
f(3)=
𝑓
(
3
)
=
Substitute in for x

f(3)=
𝑓
(
3
)
=
Simplify the parenthesis

f(3)=
𝑓
(
3
)
=
Square the parenthesis

f(3)=
𝑓
(
3
)
=
Multiply

1 answer

To find \( f(3) \) for the function \( f(x) = 3(x - 4)^2 \), we will substitute \( x \) with \( 3 \) and simplify step by step.

  1. Substitute in for x: \[ f(3) = 3(3 - 4)^2 \]

  2. Simplify the parenthesis: \[ f(3) = 3(-1)^2 \]

  3. Square the parenthesis: \[ f(3) = 3(1) \]

  4. Multiply: \[ f(3) = 3 \]

So, the final result is: \[ f(3) = 3 \]